Is robot-assisted laparoscopic myomectomy limited in multiple myomas?: a feasibility for ten or more myomas - Hyunkyung Kim; Suhyun Shim; Youngbin Hwang; Minkyoung Kim; Hyejin Hwang; Younjee Chung; Hyun-Hee Cho; Mee-Ran Kim (Korean Society of Obstetrics and Gynecology, 2018)
ObjectiveTo evaluate the feasibility of robot-assisted laparoscopic myomectomy in multiple myomas over 10.MethodsA retrospective study was conducted for 662 patients who underwent robot-assisted laparoscopic myomectomy and open myomectomy by a single operator in a tertiary university hospital.ResultsA total of 30 women underwent removal of 10 or more uterine myomas by robotics and 13 patients were selected for this study. The average number of myomas removed was 13.7 (range 10-20). The maximum diameter of the myomas was 6.8 cm (range 5.0-10.0 cm). The sum of the diameters of each myoma was 34.7 cm (range 20.0-54.5 cm) and the mass of resected myomas for each case was 229.1 g (range 106.8-437.9 g). In no case was the robotic procedure converted into conventional laparoscopy or laparotomy, and all patients recovered without any major complications. In comparison with 13 cases of open myomectomy during the same period, robotic surgery took longer time than open surgery (360.5 vs. 183.8 minutes; P=0.001) but had shorter postoperative hospital days after surgery (mean 2.5 vs. 3.5 days; P=0.003).ConclusionRobot-assisted laparoscopic myomectomy could be an alternative to laparotomic myomectomy for numerous myomas over 10 in number.